Constructing Knowledge Societies : New Challenges for Tertiary Education - World Bank (Washington, DC: World Bank, 2013)
This report describes how tertiary education contributes to building up a country's capacity for participation in an increasingly knowledge-based world economy and investigates policy options for tertiary education that have the potential to enhance economic growth and reduce poverty. It examines the following questions: What is the importance of tertiary education for economic and social development? How should developing and transition countries position themselves to take full advantage of the potential contribution of tertiary education? How can the World Bank and other development agencies assist in this process? The report draws on ongoing Bank research and analysis on the dynamics of knowledge economies and on science and technology development. Using this background, it explores how countries can adapt and shape their tertiary education systems to confront successfully the combination of new and old challenges in the context of the rising significance for tertiary education of internal and international market forces. It examines the justification for continuing public support of tertiary education and the appropriate role of the state in support of knowledge-driven economic growth. Finally, it reviews the lessons from recent World Bank experience with support of tertiary education, including ways of minimizing the negative political impact of reforms, and makes recommendations for future Bank involvement.